Burden of Non-Cardiac Patients Attending Cardiac OPD at Tertiary Care Hospital (Medical Forum Monthly, 2021)
Objective: To determine the burden of non-cardiac chest pain reported at the tertiary care hospital.Study Design: Descriptive Cross sectional studyPlace and Duration of Study: This study was conducted at the Cardiac OPD of Liaquat University Hospital, Hyderabad/Jamshoro from September 2018 to November 2018 for a period of 03 months.Materials and Methods: Non-probability (Purposive) sampling technique was applied and the data was collected on pre-tested structured questionnaire after taking written informed consent from the patients presented in cardiac OPD. Ethical approval was taken from the ethical committee of LUMHS, Jamshoro. Statistical package for Social Sciences (SPSS) version 22 was used to analyze the data.Results: During the study data collection period a total number of a total 182 (43%) out of (n=424) presented with non-cardiac chest pain who fulfilled the inclusion criteria while the overall response rate were (n=154) 84.6% and all those were included in the present study. Among the participant majority 83(54%) were female compared to 71(46%) males. The age of patients ranges from 19 years to 70 years with the mean age of 43.4 years. Most 32% of patients belongs to age group of 39-48 years whereas only 13% belongs to 59 and above year age group. Majority, (34.5%) of participants having only primary education and 6% of them had some higher-level education. While half (51%) of them belongs to lower middle class families or having lower middle class economic status.Conclusion: Substantial numbers of patients were suffering from Non-cardiac chest pain (NCCP) among them female patients visited more than males, whereas majority of the patients were belonging to their middle age i.e. 39 to 48 years.